PERSEWAAN INTERNET DENGAN SISTEM ZMART BILLING PERSPEKTIF HUKUM ISLAM - Rahman Agustiana (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
The role of internet cafes is very large as the digital divide. Through internet cafes, people can easily access the Internet without having to purchase hardware. Internet cafes services utilization in Islam is a form of contract ijara>h. The proliferation of internet cafes, of course, the greater the competition between businesses. Dian_net in operations using the system